Influence of exercise test duration on the determination of v̇o₂max and exercise intensity thresholds - Silva, Gabriel Espinosa da (2025)
Maximal oxygen uptake (V̇O₂max), gas exchange threshold (GET) and respiratory compensation point (RCP) are crucial physiological markers for aerobic fitness assessment, with applications ranging from clinical patient care to elite athlete performance optimisation. Guidelines state that an incremental exercise test, to be valid, should be designed to provoke exhaustion between 8 to 12 min. Despite the lack of evidence, this premise considered the V̇O₂max detection and has been extrapolated as a requirement for measuring GET and RCP. The purpose of this thesis was to investigate the influence of ramp test duration on the determination of V̇O₂max, the incidence of V̇O₂plateau and V̇O₂max confirmation, and the GET and RCP. The experiments apply individualised running or cycling ramp tests (RRT or CRT) to achieve varying test durations in a wide range, targeting 5 to 20 min. In the first study, 10 male runners (19.5 ± 0.6 years; 64.2 ± 7.5 kg; 1.71 ± 0.06 m) performed four tests, RRT-5, RRT-10, RRT-15 and RRT-20, aimed to last 5,10, 15 and 20 min, respectively. One baseline ramp test preceded the experimental tests. For the second and third studies, 13 cyclists/triathletes (20.3 ± 1.1 years; 67.3 ± 8.9 kg; 1.76 ± 0.06 m), three females and 10 males. Participants performed a step-incremented test; three CRTs, Short, Medium and Long, aimed to last 5, 10 and 20 min, respectively; and a 3-minute “all-out” critical power test. The tests were 2 to 7 days apart and randomised in all studies. The duration of a ramp test, either running or cycling, does not affect the V̇O₂max, maximal heart rate and maximal ventilation in trained subjects within the tested range of 5.6 to 17.4 minutes (Studies 1 & 2). The incidence of the V̇O₂plateau is lower in the ramp test than previously reported. Verifying V̇O₂max through the VEP, lasting 2.4 to 5.6 minutes, further reinforces the robustness of our findings (Study 2). The ramp test duration does not affect V̇O₂ at GET or RCP; however, it does affect running velocity or the power at RCP (Studies 1 & 3)